2019
DOI: 10.2478/jtim-2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination and Guillain–Barré syndrome: Reality or fear

Abstract: Guillain–Barré syndrome (GBS) is an inflammatory disorder and an acute immune-mediated demyelinating neuropathy that causes reduced signal transmissions, progressive muscle weakness, and paralysis. The etiology of the syndrome still remains controversial and uncertain. GBS can be initiated and triggered by respiratory tract infections such as influenza, and intestinal infections such as Campylobacter jejuni. In addition, there is considerable evidence suggesting links between influenza vaccination and GBS. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 62 publications
0
39
0
Order By: Relevance
“…We included seven case series studies in which cases of GBS were identified by using specific diagnostic criteria and evaluated for previous exposure to the influenza vaccine [22][23][24][25][26][27][28]. The remaining three studies were used for basic understanding and comprehensive discussion on the pathophysiological aspect of GBS associated with the influenza vaccine [1,29,30].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We included seven case series studies in which cases of GBS were identified by using specific diagnostic criteria and evaluated for previous exposure to the influenza vaccine [22][23][24][25][26][27][28]. The remaining three studies were used for basic understanding and comprehensive discussion on the pathophysiological aspect of GBS associated with the influenza vaccine [1,29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Side effects of vaccines are a crucial factor for the acceptance of vaccination programs [30]. Influenza vaccines are not known to cause serious side effects [29]. However, since the 1976 origin of the swine influenza vaccine, various studies have been conducted worldwide to estimate the risk of GBS following different types of influenza vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This process is the leading risk factor for the development of nerve dysfunction in Guillain-Barré syndrome. Interestingly, an unfortunate occurrence of this neurological disease was also seen in several people after vaccination with the swine flu vaccine contaminated with GM1 from Campylobacter jejuni [47,48].…”
Section: Microbial Interactions With Glycosphingolipidsmentioning
confidence: 98%